2021
DOI: 10.1097/olq.0000000000001444
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sexual Behavior Related to the COVID-19 Stay-at-Home Orders Among Young Black Men Who Have Sex With Women in New Orleans, LA

Abstract: Background: COVID-19 stay-at-home orders enacted in New Orleans, LA on March 16, 2020, may have caused changes in the way young men interacted with sex partners.Methods: An online substudy was conducted (May 21, 2020 to June 9, 2020) among Black men who have sex with women, 18 years and older, and who had previously enrolled in the parent study Check It (May 17, 2017 to March 6, 2020) to assess changes in sexual behavior during the stay-at-home orders.Results: Among 111 participants, from enrollment in Check I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 24 publications
(51 reference statements)
2
18
0
Order By: Relevance
“…Approximately 74%–87% of people reported that condom use with a steady and/or casual partner stayed the same during these 2 periods. Maintenance of pre–COVID-19 condom use behavior is consistent with observational studies of sex workers and ethnic and racial minority groups [ 20 , 21 ]. Given that COVID-19 introduced new disease risks, some individuals may have been less likely to engage in risky sexual behaviors [ 22 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Approximately 74%–87% of people reported that condom use with a steady and/or casual partner stayed the same during these 2 periods. Maintenance of pre–COVID-19 condom use behavior is consistent with observational studies of sex workers and ethnic and racial minority groups [ 20 , 21 ]. Given that COVID-19 introduced new disease risks, some individuals may have been less likely to engage in risky sexual behaviors [ 22 ].…”
Section: Discussionsupporting
confidence: 80%
“…Maintenance of pre-COVID-19 condom use behavior is consistent with observational studies from sex workers and ethnic and racial minority groups. 18,19 Given that COVID-19 introduced many new infectious disease risks, some individuals may have been less likely to engage in risky sexual behaviors. 20 Only 8.7% of the sample noted problems accessing condoms.…”
Section: Discussionmentioning
confidence: 99%
“…These shifts in partner type, however, returned to the prerestriction levels once the measures were lifted. Craig-Kuhn et al 15 studied changes in sexual behavior in heterosexual males during COVID-19 stay-at-home orders. They also found a reduction in sexual frequency and that only 27.9% had seen information about safe sex during the pandemic, indicating that the information provision on sexual distancing during the pandemic should be emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, most youth surveyed were not sexually active, participating in online dating, or sexting, before or during the pandemic. Previous studies in adult populations found significant declines in sexual activity during the pandemic, although adults did not completely stop engaging in sexual activity [11][12][13][14]. Further research is needed to understand the impact of the end of pandemic restrictions on adolescents' romantic relationships and sexual behaviors, as researchers have posited there may be a "catch-up period" in which sexual behavior increases [10].…”
Section: Discussionmentioning
confidence: 98%
“…Researchers have posited that social distancing and stay-at-home guidelines have resulted in less partnered sex for most young people as they face increased parental monitoring and reduced privacy [10]. Studies in adult populations have found evidence of significant declines in sexual activity during the pandemic, although adults did not completely stop engaging in sexual activities [11][12][13][14], as well as evidence of increased romantic relationship conflict [15,16]. Comparatively few studies in this area have included adolescent or young adult populations.…”
Section: Introductionmentioning
confidence: 99%